Evaluation of immunization coverage and its determinants in children aged 12-24 months from rural and urban areas of Udaipur, Rajasthan, India - Pahwa, Hartesh Singh; Goyal, Dileep; Sareen, Devendra (International Journal of Contemporary Pediatrics, 2019)
Background: Infectious diseases are now the world’s biggest killer of children and young adults. Over the last three decades a lot of progress has been made globally as far as protection against six important vaccine preventable diseases is concerned. The major cause of non-immunization and partial immunization in most of the studies conducted in India and abroad suggest lack of knowledge and awareness about vaccination in the community. Methods: 400 children aged 12-24 months from urban and rural areas (200 each) of Udaipur in a randomized manner were included in this study. For coverage and evaluation of vaccination in this study, informants preferably mothers were interviewed using pre-coded and pretested questionnaire by door to door visit from 1st April 2017 to 31st March 2018, in urban and rural areas of Udaipur and if mother was not available then father or any other person >18 years belonging to the household was asked to respond to questionnaire. Results: The present study was undertaken to find out the vaccination coverage in eligible population in rural and urban blocks of Udaipur. Out of 400 children evaluated. More than half (60.25%) of children were completely immunized. 29.5% children were partially immunized and 10.25% were not immunized at all. Conclusions: Lack of knowledge and awareness were the main reason for non-immunization (44.4%) and partial immunization (29.4%) respectively.